'I've tempted the saint with my prayer!' Prayer, charisma and ethics in Romanian eastern orthodox Christianity. Issue 1 (2nd January 2017) - Pop, Simion
ABSTRACT: Marcel Mauss' perspective on prayer has the merit of revealing the complex relations between individual experience, sociality and efficacy of prayer. In this article I propose a particular ethical perspective on prayer and these complex relations and also a new ethnographic territory for studying situational, relational and personal practices of prayer. Considering the ethical orientation towards contemporary saints within the Romanian Eastern Orthodox revival milieu I introduce the notion of charismatic exemplar in order to open up the analytical space for studying prayer as ethical practice. I argue that relational ethics reveals that prayer practices work efficaciously within the everyday web of constitutive ethical relationships and are replete with ethical insights into these relationships' concrete social and historical constitution. Within the Orthodox revival milieu the ethical capacities of engaging in social relationships are prayerfully shaped at the intersection of self-cultivation in terms of an authoritative tradition, charismatic authority/exemplarity and social-historical conditions.